Faktor-Faktor Yang Berhubungan Dengan Aktivitas Enzim Cholinesterase Darah Pada Petani Penyemprot Pestisida - Christien Gloria Tutu; Aaltje Ellen Manapiring; Adrian Umboh (Indonesian Journal of Public Health and Community Medicine, 2020)
Background: One of the parameters for pesticide poisoning is the decrease in the activity of the cholinesterase enzyme. A decrease in cholinesterase activity of 30% from normal was considered poisonous. Rurukan Village is a center for horticultural production, farmers in Rurukan Village tend to be exposed to pesticides frequently so that they have a large enough chance of experiencing pesticide poisoning. This study aims to analyze what factors are related to the activity of the cholinesterase enzyme in pesticide spraying farmers in Rurukan Village, East Tomohon District, Tomohon City.Method: This type of research is a laboratory-based observational analytic study with a cross sectional study approach. Samples were taken from 30 pesticide spraying farmers in Rurukan Village. The sampling technique used purposive sampling. The data was collected by examining the farmers' blood cholinesterase levels by health workers from the Prodia Manado laboratory and interviewing using a questionnaire. Data were analyzed bivariate and multivariate.Result: The result showedit known that there is no relationship between age and cholinesterase enzyme activity (p = 0.440; OR = 0.455); there is no relationship between knowledge and cholinesterase enzyme activity (p = 0.400; OR = 1,000); there is a relationship between working period and cholinesterase enzyme activity (p = 0.032; OR = 7.500); there is a relationship between spray duration and cholinesterase enzyme activity (p = 0.004; OR = 14.875); there is a relationship between spray frequency and cholinesterase enzyme activity (p = 0.013; OR = 11,200); there is a relationship between the use of PPE with cholinesterase enzyme activity (p = 0.002; OR = 21,000); there was no relationship between the direction of spraying and the cholinesterase enzyme activity (p = 0.637; OR = 2.500).Conclusion:In this study, it can be concluded that the relationship between the factors causing the decrease in cholinesterase enzyme activity in pesticide spraying farmers in Rurukan Village obtained a significant relationship between working tenure, spray duration, spray frequency and use of PPE with cholinesterase enzyme activity. The use of PPE is a factor that is most closely related to the activity of the cholinesterase enzyme in pesticide spraying farmers in Rurukan Village.